2020
DOI: 10.1038/s41598-020-61007-0
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome of the diatom Cylindrotheca closterium identifies genes involved in the metabolism of anti-inflammatory compounds

Abstract: Diatoms are the most diverse and abundant group of phytoplankton species and represent a huge reservoir of marine natural products with possible application for human health. Several diatoms are known to have anticancer, anti-inflammatory, antioxidant and anti-microbial properties, but the compounds responsible of these activities are often still unknown. The diatom Cylindrotheca closterium showed anti-inflammatory properties inhibiting TNFα release in human monocytic leukemia cells. In this study, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Initial cell concentration for each bottle was about 5000 cells/mL. Culture growth was monitored daily by sampling 2 mL of culture, and fixing with one drop of Lugol (final concentration of about 2%, v / v ) and counting cell numbers in a Bürker counting chamber under an Axioskop 2 microscope (20×) (Carl Zeiss GmbH, Oberkochen, Germany) (as in Elagoz et al [ 108 ]). The growth curve of Alexandrium tamutum (in control and P-starvation conditions) is available in Figure S3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial cell concentration for each bottle was about 5000 cells/mL. Culture growth was monitored daily by sampling 2 mL of culture, and fixing with one drop of Lugol (final concentration of about 2%, v / v ) and counting cell numbers in a Bürker counting chamber under an Axioskop 2 microscope (20×) (Carl Zeiss GmbH, Oberkochen, Germany) (as in Elagoz et al [ 108 ]). The growth curve of Alexandrium tamutum (in control and P-starvation conditions) is available in Figure S3 .…”
Section: Methodsmentioning
confidence: 99%
“…Experimental culturing for both control and P-starvation conditions was performed in 2 litre polycarbonate bottles (each condition was performed in biological triplicates), constantly bubbled with air filtered through 0.2 µm membrane filters. For the control condition, normal K medium was used, while for the P-starvation experiment, the K medium was prepared with low concentrations of phosphate (0.5 µM PO 4 2− rather than 36 µM PO 4 2− of the control condition [108]). The growth curve of Alexandrium tamutum (in control and P-starvation conditions) is available in Figure S3.…”
Section: Cell Culturing and Harvestingmentioning
confidence: 99%
“…Recent studies showed that microalgae produce metabolites with anticancer [5], anti-inflammatory [6], anti-diabetes [7], antioxidant [8], anti-tuberculosis [9], anti-epilepsy [10], anti-hypertensive [8], anti-atherosclerosis [8] anti-osteoporosis [8] and immunomodulatory activities [11,12]. In addition, various authors showed that different nutrient culturing conditions could influence microalgae bioactivities [6,13], triggering the activation of specific metabolic pathways [14][15][16][17]. These studies showed that the bioactivity of microalgae is not correlated with a specific microalgae class or a specific culturing condition, but depends on the microalgae clone, the algal growth phase, the culturing condition and chemical extraction protocol used, and should be carefully considered case by case.…”
Section: Introductionmentioning
confidence: 99%
“…They are also known to produce a plethora of metabolites derived from primary and secondary metabolism, which have shown possible applications for human health (e.g., compounds with anti-cancer, anti-microbial, anti-diabetes, anti-epilepsy, anti-inflammatory, anti-atherosclerosis, anti-osteoporosis, immunomodulatory and antioxidant activities; [1][2][3][4][5][6][7][8][9][10]). Various studies have focused on the discovery of metabolic pathways involved in the synthesis of bioactive compounds [11][12][13][14]. Even if microalgae can be cultured in big volumes to get large amounts of the compounds of interest, heterologous expression of the enzyme responsible for the compound synthesis and its production in a host can be a valuable alternative for meeting industrial demands.…”
Section: Introductionmentioning
confidence: 99%